1984
DOI: 10.1128/iai.45.2.491-497.1984
|View full text |Cite
|
Sign up to set email alerts
|

Sequential metabolic alterations in the myocardium during influenza and tularemia in mice

Abstract: Mice with generalized influenza or tularemia of similar lethality were studied in an effort to compare biochemical responses of the myocardium during infections of viral and bacterial etiology. A progressive loss of body weight characterized the course of both infections. Accompanying this, the myocardial content of protein and the activities of lactate dehydrogenase, citrate synthase, and cytochrome c oxidase all decreased. However, myocardial protein degradation appeared earlier and was more pronounced in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…The skeletal muscles, which constitute approximately 45% of bodyweight, are the major source of amino acids, 14 but the heart muscle also contributes (Figure 1). 18 , 19 , 20 Thus, a decrease in the protein content of the skeletal muscles, as well as in that of the heart muscle, is a general feature in acute infectious diseases, the magnitude of which is related to the magnitude and duration of the systemic acute phase reaction of the host. In acute myocarditis, this wasting of myocardial muscle protein occurs in parallel with the microorganism‐ and inflammation‐related damage to the heart.…”
Section: The Neuromuscular System In Infectionsmentioning
confidence: 99%
“…The skeletal muscles, which constitute approximately 45% of bodyweight, are the major source of amino acids, 14 but the heart muscle also contributes (Figure 1). 18 , 19 , 20 Thus, a decrease in the protein content of the skeletal muscles, as well as in that of the heart muscle, is a general feature in acute infectious diseases, the magnitude of which is related to the magnitude and duration of the systemic acute phase reaction of the host. In acute myocarditis, this wasting of myocardial muscle protein occurs in parallel with the microorganism‐ and inflammation‐related damage to the heart.…”
Section: The Neuromuscular System In Infectionsmentioning
confidence: 99%
“…Several aspects of the mnetabolic response of the host to the stress of any infection are stereotyped and predictable (W. R. Beisel [in M. C. Linder, ed., Nutrition and Infection, in press]), but in a recent study, important differences were observed in the response of the myocardium to influenza and tularemia (20). Thus, more pronounced tissue wasting and concomitant decreases in metabolic capacity occurred in influenza than in tularemia, the catabolic responses to these two infections possibly being mediated by different metabolic pathways (20). * Corresponding author.…”
mentioning
confidence: 99%
“…A second purpose was to study the effects of forced exercise in the acute phase of the same infections on myocardial histology, biochemistry, and lethality in trials 3 to 6. Influenza and tularemia of similar intensities were used in mouse models, since myocarditis is not a feature of these infections in resting rodents (14,20).…”
mentioning
confidence: 99%
“…These horses also had a higher rate of weight loss and loss of body condition, suggesting that protein catabolism may have contributed to a loss in lean body mass. In mice infected with influenza virus, decreased protein synthesis and increased protein degradation may contribute to the observed myocardial muscle wasting 38 …”
Section: Discussionmentioning
confidence: 99%